Peningkatan Wawasan Kimia Organik dalam Menunjang Pembelajaran Kimia di SMA - Kristanti, Alfinda Novi; Aminah, Nanik Siti; Suwito, Hery (FMIPA Universitas Lampung, 2022)
The role of practical work in Organic Chemistry is to provide experience to gain skills and to reinforce concepts that have been obtained from theory and also to increase understanding and to increase interest or motivation. However, practical work has not been an activity that can always be done in high school, especially for chemistry due to facility lack. For this reason, a workshop is needed to increase the understanding of high school chemistry teachers in basic Organic Chemistry, as well as to increase the insight of chemistry teachers in creating practical topics that are in accordance with the facilities available at school. The workshop was held for high school chemistry teachers in Mojokerto. The workshop consisted of an explanation of the basic of Organic Chemistry and the use of Chem Office software, accompanied by practical work in laboratory. The workshop held was successfully added the insights of the teachers and it was hoped that the knowledge obtained would be applied in learning process in their respective high schools.